2019
DOI: 10.6002/ect.2017.0214
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Care Professionals’ Attitude Toward the Presumed Consent System

Abstract: Health care professionals in Malaysia have a relatively negative attitude toward the presumed consent system, which does not encourage the implementation of this system in the country at present. To pave the way for a successful implementation of the presumed consent system, efforts should be initiated to enhance the attitude of health care professionals toward this system. In particular, these efforts should at most target the health care professionals who are Malay, earn a low income, and have a negative def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Many healthcare professionals are also against implementing a presumed consent system despite supporting organ donation. Tumin et al ( 23 ) found that almost half (45.8%) of the surveyed healthcare professionals objected to donating their organs if a presumed consent system was in place, with most of them who were initially unwilling to donate were from the Malay ethnic group or had incomes of RM3,000 or lower. Malaysia is not ready to move towards a presumed consent system if healthcare professionals are not keen on the idea, as they are a major factor in organ donation advocacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many healthcare professionals are also against implementing a presumed consent system despite supporting organ donation. Tumin et al ( 23 ) found that almost half (45.8%) of the surveyed healthcare professionals objected to donating their organs if a presumed consent system was in place, with most of them who were initially unwilling to donate were from the Malay ethnic group or had incomes of RM3,000 or lower. Malaysia is not ready to move towards a presumed consent system if healthcare professionals are not keen on the idea, as they are a major factor in organ donation advocacy.…”
Section: Discussionmentioning
confidence: 99%
“…Malaysia is not ready to move towards a presumed consent system if healthcare professionals are not keen on the idea, as they are a major factor in organ donation advocacy. More studies should be done to understand this pattern to identify solutions and raise confidence in the organ donation system ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the opinion of health care professionals on donation legislative systems is critical in this context, as they play a vital role in facilitating the process of donation and transplantation. 5 Although the findings of Cheung et al 2 are imperative, more accurate policy recommendations in this context require further studies to investigate willingness to donate under an opt-out system with allocation priority as well as health care professionals' opinion of donation legislative systems in Hong Kong.…”
Section: In Search Of the Best Organ Donation Legislative System For mentioning
confidence: 99%